Dynamics of the Development of Mineral and Coal Mining Legal Policy Management by Regional Governments - Rahardjo, Anthony; Herman, KMS (Pelopor Publikasi Akademika, 2025)
This research aims to analyze the dynamics of mining policy in Indonesia from the colonial era to the modern era, focusing on regulatory changes, their impact on the national and regional economies, and the challenges in managing mining resources. The research method used is a normative juridical method with a legislative approach (statute approach) and a historical study involving an analysis of various legal regulations, from the Indische Mijnwet 1899 to the latest Minerba Law. The results show that Indonesia’s mining policies have undergone significant changes, from colonial exploitation that benefited the Dutch East Indies government, to post-independence nationalization facing technological and capital limitations, and to openness to foreign investment during the New Order era, which accelerated the growth of the mining industry but led to regional economic imbalances and environmental degradation. Reform brought decentralization of authority to regional governments, which, on one hand, increased local revenues but also caused governance issues due to weak oversight. To address this, the government regained full control over the mining sector through the Minerba Law to ensure effective management and legal certainty for investors. However, the main challenge still faced is how to balance national interests, regional welfare, and environmental sustainability so that mining resources can be managed fairly and sustainably.